Analisis Reaksi Pasar Modal terhadap Pemilihan Umum Presiden Indonesia Tahun 2024 - Rasyid, Syarifuddin; Darmawati, Darmawati; Khaerany, Rizky; Nadhifa, Nisrinatul; Pratiwi, Dwi Dian (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research seeks to assess the capital market's response to the Indonesian presidential election by employing an event study methodology that incorporates abnormal return (AR) and trading volume activity (TVA) variables.Methodology/approach: This research employs a quantitative methodology utilising the event study technique on the Indonesia Stock Exchange. The utilised data comprises stock price information and trading volumes of companies listed in the LQ45 index. This study utilised a sample size of 45 companies. The employed hypothesis tests are the Wilcoxon Signed Ranks Test and the One Sample t-test.Results/findings: There is no significant market reaction in the days surrounding the 2024 election. There is a significant difference in abnormal returns before and after the 2024 election, but this difference is not followed by a difference in trading volume activity. In this study, there is no significant difference in trading volume activity before and after the 2024 presidential election.Conclusions: The capital market reaction to the presidential election on February 14, 2024 in Indonesia can be concluded that there was no significant market reaction in the days surrounding the 2024 election, although there was a difference in abnormal returns before and after the election.Limitations: This study's limitations include the inability to generalise results due to its exclusive focus on the LQ-45 index population and the selection of event types that inadequately represent presidential election occurrences, thereby restricting the generalisability of the election's impact on capital market reactions.Contribution: This research aims to assist investors and policymakers in comprehending market responses to political changes and their ramifications for investment choices.